IMPLEMENTASI ALGORITMA APRIORI SEBAGAI ALTERNATIF STRATEGI PROMOSI UNIVERSITAS PGRI MAHADEWA INDONESIA - Ida Ayu Putu Febri Imawati; Budhya Wirandha Gupta; I Kadek Juni Arta; I Wayan Dika (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
UPMI Bali is a new campus, so campus promotion is still very much needed to increase prospective new students at UPMI Bali. By utilizing available data, the campus can determine effective campus promotion strategies using data mining. The data system will be built using the Association Rules technique. Association Rules is a data mining method to find frequently occurring association patterns in data. This method is popular because it is often used to analyze shopping carts. The rules formed will be in the form of